Measurement of Phenotype Characteristics of Sasak Ducks: Indian Runner Ducks of Lombok Island Indonesia - Tamzil, Mohammad Hasil; Indarsih, Budi (ANIMAL PRODUCTION, 2017)
This study was designed to determine the phenotype characteristics of Sasak ducks in Lombok Island. Â The study used 64 Sasak ducks at production stage which were kept intensively by small holder farmers. Observations on the characteristics of the feather color were carried out directly on each animal. The data observed were feather colors, beak color, and the color of the foot and shank, while the data on the size of the body that was observed were body weight, beak length, neck length, back length, breast circumference, back length, thigh length, shank length, and the distance between the two pubic bones. The data obtained were tabulated and analyzed descriptively. The study concluded that the characteristic of the color of feathers in Sasak ducks were dominated by Roman color (50.13%), followed by Tanak color (21.87%), Tongkak color (15.63%), Rombak color (6.25%), and Cemaning color (3.12%). Â Sasak ducks with medium size were observed to have a relatively long beak, medium-long neck, short back, broad and deep chest, medium height, and the distance between the two pubic bones was quite wide. These characteristics indicate that Sasak ducks are the type of superior Indian Runner having better production ability compared to the other types of Indian Runner duck.Â